UPAYA MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN DENGAN METODE SILABA DI KELAS I SD NEGERI KARANGLEWAS KIDUL - Rokhayah (Pusat Studi Pendidikan dan Kreativitas Guru, 2018)
Learning by the SILABA method is a process of beginning readinglearning that begins with syllable recognition, such as ba, bi, bu, be, bo, ca, ci,cu ce, co and so on, then the syllables are coupled into meaningful words. Themethod is used to determine the ability to read the beginning and the livelinessof students on learning in class I SD Negeri Karanglewas Kidul. The issues thatare the focus of improvement are (1) how the teacher’s actions use the SILABAmethod; (2) How much students’ ability to read in the beginning; (3) how highthe student activeness increase in learning. Where it is done through a processof cycling assessment called a cycle. Each cycle consists of planning, execution,observation and reflection. Improvement of learning is done in 2 cycles. Thefindings of this study are (1) Teacher action in cycle II of 85.94%, so it hasexceeded the indicator set ie 61-80%; (2) The reading ability has also exceededthe indicator, 70% of students have the ability to read sentences, 80% of studentshave the ability to read words and 100% students read syllabic skills; (3) Andthe activity of students has exceeded 70% that is 81%.